Yield Response of Sweet Potato ( Ipomoea batatas L.) Genotypes Cultivated in Post‐Rice Paddy Field - Ruttanachira Ruttanaprasert; Wanwipa Pinta; Lakkana Pitak; Anon Janket; Darika Bunphan; Chorkaew Aninbon (International Journal of Agronomy, 2025)
Sweet potatoes ( Ipomoea batatas L.) are a nutrient‐rich root crop with substantial nutritional, economic, and environmental benefits. This study assessed nine sweet potato genotypes across three distinct locations in Thailand to evaluate yield potential, adaptability, and environmental influences. Trials used a randomized complete block design with four replications. Location 1 (Thatum District) featured sandy soil with moderate pH, high salinity, and balanced nutrients but lower phosphorus (P) and nitrogen (N). Location 2 (Maung District) had sandy, acidic soil but was the most chemically fertile, with high P and potassium (K). Location 3 (Rajamangala University of Technology Isan, Surin Campus) had loamy sand with higher silt content, acidic pH, low P, K, and electrical conductivity (EC). Results highlighted significant yield differences influenced by soil and environmental variability. Genotype SR18003 achieved the highest yield and harvest index, demonstrating strong adaptability and commercial potential. Strong correlations between storage root traits (number, size, and weight) indicate their usefulness for selection. The study underscores the importance of tailored soil management and location‐specific genotypes in optimizing sweet potato production, contributing to resilient varieties, sustainable farming, and improved food security. Further research on genetics and agronomy can enhance breeding and cultivation systems.
Keywords: Growth and nutrition in plants; Potato Plant Research; Banana Cultivation and Research